UPAYA PREVENTIF DALAM MENEKAN INSIDEN TENAGA KERJA INDONESIA DI MALAYSIA MELALUI HUBUNGAN BILATERAL INDONESIA DAN MALAYSIA - Sintya Dewi, Gusti Ayu Nyoman; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
The issue of migrant workers has always heated up relations between the two countries due to the actions of some officials and the people in Malaysia who were arbitrarily assessed. This study aims to analyze Preventive Efforts in Suppressing the incidence of TKIs with problems in Malaysia in 2014-2017. In this study, the data collection technique that I use is library research. The result show that the efforts that have been made by the Government of Indonesia are to conduct bilateral cooperation between Indonesia-Malaysia through the signing of the MoU. After the collaboration in the form of the MoU, cooperation was also carried out in the form of the coming of Letter of Intent (LOI). This means that preventive factors involve mechanisms, procedures, the process of awareness (socialization) becomes an important part as a preventive aspect to suppress the incident or problem of migrant workers. Keyword: preventive efforts, migrant workers, bilateral relations